Effectiveness of Argan Oil Consumption on Knee Osteoarthritis Symptoms: A Randomized Controlled Clinical Trial - Essouiri, Jamila; Harzy, Taoufik; Benaicha, Nadia; Errasfa, Mourad; Abourazzak, Fatima E. (Current Rheumatology Reviews, 2017)
Background: Knee osteoarthritis (KOA) is a common chronic degenerative disorder. It causes joint pain, walking difficulties and a decline in general physical function. Many pain drugs and treatment modalities can be prescribed for KOA. Among traditional medicines in Morocco, Argan oil has been used in the treatment of knee osteoarthritis to reduce pain and improve physical activity, though there have been no medical-based evidence for such treatment. Argan oil is known to have anti-oxidant and lipid modulatory properties due to its content of many substances, such as tocopherols, phytosterols, saturated and unsaturated fatty acids. Objectives: This study was undertaken in order to investigate the effect of daily consumption of culinary argan oil on KOA symptoms. Patients and Methods: We conducted a randomized controlled clinical trial on patients with KOA according to the American College of Rheumatology (ACR) criteria. Patients were divided into 2 groups: argan oil group who received argan oil to be consumed every morning (30 ml per day) for 8 weeks and control group with no treatment. Clinical assessment before and after 8 weeks study was performed by several tests such as the Visual Analogue Scale (VAS) for pain, walking perimeter, the Western Ontario and McMaster Universities osteoarthritis index (WOMAC), and the Lequesne index. Results: The study included 100 patients. 51 patients were randomly assigned to argan oilgroup while 49 patients were randomly assigned to control group with no treatment. Mean age of our patients was 58.24 ± 7.2 years, with a majority of women (93%). Following 8 weeks of argan oil consumption, argan oil group had a very significant decrease of VAS for pain (p< 0.0001), with a significant decrease in WOMAC pain index (p < 0.0001), and improvement of WOMAC function index (p < 0.0001). Lequesne index (p < 0.0001) as well as walking distance (p =0,002) significantly improved. When data of argan oil group were compared to those of control group, we found statistically significant differences in all the above measured parameters: VAS of pain (P=0,02), WOMAC pain (p<0,0001), WOMAC function (p<0,0001), walking distance (p=0,001) and lequesne index (p<0,0001). Conclusion: Patient's consumption of argan oil seems to be safe and efficacious in improving clinical symptoms of KOA.
Keywords: knee osteoarthritis